Illinois materials, Anthony F. C. Wallace Papers - Wallace, Anthony F. C., 1923-2015; Kane, Michal Lowenfels; Rochmes, Louis (1949)
The Anthony F. C. Wallace Papers are a vast collection of materials relating to Wallace's work at the intersection of anthropology, psychology, and history. Though further research might yield more results, approximately 17 items directly pertaining to the related Algonquian peoples known as the Illinois have been identified. Most of these materials are located in Series IX. Indian Claims, and relate to Wallace's work as a researcher and expert witness on behalf of Native American land claims. They include research note cards (located in Series III. Notecards), research notes and write-ups, copies and extracts of primary sources, court dockets, trial memoranda, tribal histories, and correspondence with historical societies and legal representives of the claimants. There are also materials relating specifically to the Peoria and Kaskaskia peoples of the Illinois, including dockets naming them as claimants, trial memoranda, and research notes. Note that much of Wallace's material on the Illinois also mentions the Miami, Iowa, Sac and Fox (Meskwaki), and other neighboring peoples, and that there is a great deal of overlap in these entries. See also the Louis Rochmes file in Series I. Correspondence. See the finding aid for a detailed discussion of Wallace's long and varied career, and for an itemized list of the collection's contents.